2013
DOI: 10.6061/clinics/2013(03)oa15
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A levels in hyperthyroidism

Abstract: OBJECTIVE:Fetuin-A is a protein secreted from the liver that inhibits arterial calcification deposition and can contribute to insulin resistance. Hyperthyroidism is also associated with insulin resistance. It is not known whether hyperthyroidism has an effect on fetuin-A levels.METHODS:We measured fetuin-A levels and homeostasis model of assessment-insulin resistance before hyperthyroidism treatment was initiated and after euthyroidism was achieved. A total of 42 patients diagnosed with hyperthyroidism were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Reported associations between thyroid function and serum fetuin-A levels were inconsistent in previous studies. [3841] Pamuk et al [38] reported that fetuin-A levels in patients with hyperthyroidism decreased after achieving euthyroidism. The basal fetuin-A levels were positively associated with basal fT4 and negatively correlated with basal TSH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reported associations between thyroid function and serum fetuin-A levels were inconsistent in previous studies. [3841] Pamuk et al [38] reported that fetuin-A levels in patients with hyperthyroidism decreased after achieving euthyroidism. The basal fetuin-A levels were positively associated with basal fT4 and negatively correlated with basal TSH.…”
Section: Discussionmentioning
confidence: 99%
“…The basal fetuin-A levels were positively associated with basal fT4 and negatively correlated with basal TSH. [38] Without recruiting euthyroid controls, there were no comparisons between fetuin-A levels in hyperthyroid or euthyroid patients in that study. [38] The correlations between fetuin-A and fT4 or TSH after treatment were also not evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fetuin-A is a prominent serum glycoprotein and a major non-collagenous component of mineralized bone in mammals. Fetuin-A can inhibit or stimulate osteogenesi sin vitro, depending on its concentrations (47).…”
Section: Fetuin-a Vs Cationsmentioning
confidence: 99%